Versatile and Marvelous Potentials of Polydeoxyribonucleotide for Tissue Engineering and Regeneration - Oh, Nuri; Hwang, Juyoung; Kang, Moon Sung; Yoo, Chung Yul; Kwak, Minseok; Han, Dong Wook (Biomaterials Research, 2025)
Over the past decade, substantial focus has been placed on polydeoxyribonucleotide (PDRN) due to its promising pharmacological properties, making it a valuable candidate for tissue engineering applications. Accordingly, this paper aims to review and summarize the latest experimental research on PDRN in the context of tissue engineering and regeneration. The unique biochemical mechanisms of PDRN to promote cellular behavior and regeneration are summarized. We categorize commonly utilized PDRN-based tissue engineering fields as neuromuscular tissues, diabetic wound or skin, and bone regeneration. At the same time, we explore scaffold strategies for integrating PDRN into bioceramics, polymers, and cell/tissue-derived materials, along with its combination with photo/electromodulation techniques. Furthermore, we discuss potential opportunities and challenges in translating PDRN-based approaches into clinical practice. We expect future interdisciplinary research and clinical trials to evaluate the long-term efficacy and safety of PDRN while emphasizing standardization and quality control to ensure its consistency and effectiveness in regenerative applications.